Impact of antimicrobial stewardship interventions on days of therapy and guideline adherence: A comparative point-prevalence survey assessment - Shamseddine, Jinan; Sadeq, Ahmed; Yousuf, Khadija; Abukhater, Rawan; Yahya, Lamia Omer; Espil, Maysaa Abdulatif; Hassan, Mohamed Elamin; Fadl, Rayan Elamin; Ahmed, Rami Tag Elsir; Elkonaissi, Islam; Abdelsalam, Abeer Elmahi; Naqbi, Aisha Al; et al. (Frontiers in Tropical Diseases, 2023)
Background Antimicrobial stewardship (AMS) is a crucial tool for rationalizing the use of antimicrobial agents and reducing the burden of antimicrobial resistance. We aimed to assess the impact of AMS interventions on antimicrobial utilization and adherence to antimicrobial guidelines. Methods We conducted a prospective quasi-experimental study at a major tertiary hospital in the United Arab Emirates. Using standardized World Health Organization’s methodology, point-prevalence surveys (PPS) were performed in November 2019 and January 2022. Core AMS interventions consisted of proactive bloodstream infection service, proactive and reactive infectious diseases consult service, prospective audit and feedback by clinical pharmacists, development of antimicrobial guidelines based on cumulative antibiograms, and implementation of induction programs for new clinical staff. Days of therapy (DOT) per 1000 patient days present and rate of compliance with antimicrobial guidelines were compared before and after the core interventions. Multiple logistic regression analysis was carried out to adjust for the potential confounding effects of age, gender, hospitalization within 90 days, central or peripheral line insertion, urinary catheterization, and mechanical ventilation. P-value<0.05 was considered statistically significant. Results Pre- and post-intervention PPSs included 292 and 370 patients, respectively. Both had similar age and gender distribution. Patients receiving antimicrobials were 51% (149/292) in 2019 and 45% (166/370) in 2022 (p 0.12). Univariate analysis showed a reduced post-intervention DOT per 1000 patients present (6.1 +/- 16.2 vs 2.4 +/-5.1, p<0.01) and an improved post-intervention guideline compliance (59% vs 67%, p 0.23). Following multiple logistic regression, the reduction in post-intervention DOT remained statistically significant (co-efficient -0.17 (95% CI -8.58 to -1.94, p<0.01), and the improvement in guideline adherence became statistically significant (adjusted odds ratio 1.91 (95% CI 1.05 to 3.45, p 0.03). Conclusion Coordinated and sustained AMS interventions have a significant impact on improving antimicrobial utilisation and adherence to guidelines.